Optimizing Function Point Analysis in Moodle: A Plugin-Based Solution for Automated Grading and Student Assessment - Firdaus, Lukmannul Hakim; Wisnuadhi, Bambang; Rahmani, Ani (Media Jurnal Informatika, 2025)
Learning Management Systems (LMS), especially Moodle, have become integral tools in modern education, enabling efficient management of teaching materials, assignments, and assessments. This study aimed to develop and integrate a Moodle plugin for automating Function Point (FP) calculations, a method used in software engineering education to estimate development complexity. The research focused on creating an Activity Module plugin that automates the FP calculation process, reduces manual grading efforts, and provides immediate feedback to students. The plugin underwent functional testing, including Requirement Verification, UI Testing, Integration Testing, and Output Validation, to assess its performance. The results demonstrated that the plugin successfully automated the calculation of Unadjusted Function Points (UFP) and Value Adjustment Factor (VAF), with accurate results and seamless integration into Moodle’s core modules such as assignment creation, grading, and user management. Testing confirmed that the plugin met all functional requirements, and the UI and integration worked as intended. The study concluded that the FP plugin is a viable alternative to traditional FP instruction, delivering time saved, error reduction, and reduced manual grading effort. Limitations of the study include the small-scale testing, and future research should focus on evaluating scalability for larger classes and assessing its impact on student learning outcomes. Further development could explore integrating advanced features like analytics and AI-assisted feedback to enhance the learning experience.